2020
DOI: 10.3390/su12010384
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Stability of Performance of Wheat Population Varieties Developed by Participatory Breeding

Abstract: Modern agricultural systems rely on reduced crop genetic diversity, due in particular to the use of homogeneous elite varieties grown in large areas. However, genetic diversity within fields is a lever for a more sustainable production, allowing greater stability and resistance to biotic and abiotic stresses. In France, a Participatory Plant Breeding (PPB) project on bread wheat, involving farmers, facilitators and researchers, has led to the development of heterogeneous populations whose within-variety geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 75 publications
0
12
0
1
Order By: Relevance
“…The high contribution of the genotype to the variation of TKW and plant height indicates that for the studied DH lines these two traits are most stable compared with ear emergence. Van Frank et al (2020), found a close stability of breeding populations and commercial varieties for plant height and TKW. Barbu et al (2018) reported that the reduced plant height and its stability in wheat were not correlated with the genetic background of this trait.…”
Section: Discussion Discussion Discussionmentioning
confidence: 81%
“…The high contribution of the genotype to the variation of TKW and plant height indicates that for the studied DH lines these two traits are most stable compared with ear emergence. Van Frank et al (2020), found a close stability of breeding populations and commercial varieties for plant height and TKW. Barbu et al (2018) reported that the reduced plant height and its stability in wheat were not correlated with the genetic background of this trait.…”
Section: Discussion Discussion Discussionmentioning
confidence: 81%
“…It should also be noted that the landraces displayed a large heterogeneity in the δ 15 N signal compared to the CVs, which could be due to their higher genetic variability [76] coupled with the aforementioned N redistribution from the ears and protein degradation of other plant parts [49]. The importance of the N redistribution mechanisms in the grain N should be considered for future plant breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the phytochemical and micronutrient content of wheat seems to be strongly influenced by its genetics, the environment and interactions between genetics and the environment profoundly influence this content. Results are now available on agronomic variety trials across the world [23,[33][34][35][36]. These confirm the wide adaptive potential of populations but few results have been released on the nutritional and sensory characteristics of genetically diverse varieties in different growing environments.…”
Section: Introductionmentioning
confidence: 85%
“…One organic farming strategy is to diversify intra-specific genetic diversity to stabilize yield by reintroducing landraces and genetically heterogeneous varieties [23] and by growing variety mixtures. Indeed, population varieties are characterized by their high genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation